2019
DOI: 10.1002/tsm2.124
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maturation on the reliability of the Nordic hamstring exercise in male youth footballers

Abstract: This study sought to establish the reliability of the Nordic hamstring exercise (NHE) in male youth football players. Sixty‐four youth football players completed two x three repetitions of the NHE, separated by 1 week. Eccentric hamstring strength was during the NHE using the NordBord. Participants were categorized via maturity offset (based on peak height velocity [PHV]) and age. For all dependent variables and groups, the typical error (TE) was greater than the smallest worthwhile change. Reliability for lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…Regarding absolute reliability, the magnitude of our SEM estimates for all Nordbord measures (7-8%) was largely consistent with those previously reported in young soccer players (6-8% [16]) and in adults (6-9% [35]). For the ForceFrame, our range of SEM estimates (3-11%) encompasses the value previously reported for adult soccer players (8% [12]).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding absolute reliability, the magnitude of our SEM estimates for all Nordbord measures (7-8%) was largely consistent with those previously reported in young soccer players (6-8% [16]) and in adults (6-9% [35]). For the ForceFrame, our range of SEM estimates (3-11%) encompasses the value previously reported for adult soccer players (8% [12]).…”
Section: Discussionsupporting
confidence: 91%
“…However, to support effective decisions on training content and intensity, establishing the reliability of measures used to monitor responses to daily load is crucial ( 31 ). Although Nordbord and ForceFrame reliability have been previously reported in adult populations ( 12 , 35 ) and the Nordbord in youth footballers aged 10–16 years who were not involved in any formal strength and conditioning training ( 16 ), reliability has yet to be established in academy soccer players. The primary objective of this study was to establish the reliability of eccentric hamstring strength and isometric adductor strength tests using the Nordbord and ForceFrame, respectively, in academy-based adolescent soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…The NHE was performed on the NordBord apparatus (Vald Performance, Australia), which has been shown to be a reliable device (CV% = 6.1%-7.4%) to assess eccentric hamstrings strength in young athletes. 16 All testing occurred at the same facility, which was the university's performance gym. For the assessment of eccentric hamstrings strength, participants knelt on the padded part of the NordBord and were positioned with their ankles secured with padded hooks, which were attached to load cells.…”
Section: Eccentric Hamstrings Strengthmentioning
confidence: 99%
“…The tests used in this study have all been shown to be reliable. [22][23][24] First, standing height (Charder stadiometer, HM 200P, Taiwan) and body mass (Polar Balance Scales, 1G, Finland) were recorded to the nearest 0.1 cm and 0.1 kg, respectively. Leg length was measured to the nearest 0.1 cm with a dressmakers tape from the ASIS to the medial malleolus of the tibia of the preferred kicking leg.…”
Section: Performance Data Collectionmentioning
confidence: 99%
“…A key feature of this intervention's success is likely a consequence of the high compliance rate of the HG which was close to 3  / week with individual exercises only missed 13% of the time. Moreover, assessments of strength, power and balance were included to draw conclusions on programme effectiveness, [22][23][24] given that the number of injuries alone were considered insufficient. 17 Similar injury rates likely reflect the comparable improvements observed across the exercise assessments in HG and TG, however further research is required to investigate the true injury reduction effects in elite adolescent footballers when Part 2 of the 11+ is performed at home.…”
Section: Strengths and Limitationsmentioning
confidence: 99%